TEORI FISIKA ATOM SEBAGAI MATERI PENDIDIKAN BERDASARKAN PERSPEKTIF HADIS NABI MUHAMMAD SAW - Napsawati Napsawati; Arifuddin Ahmad; Erwin Hafid; Irma Sakti; Yusdarina Yusdarina (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2023)
Atomic Physics Theory as Educational Material Based on the Hadith Perspective of the Prophet Muhammad Saw. This study aims to understand the concept of educational material in general, hadith related to educational material, especially on the theory of atomic physics and to know the content and explanation of hadith in relation to the world of education. The method used in this study is in the form of pure literature with the techniques used in collecting data based on documentation through written heritage evidence such as writings or manuscripts, archives, books on opinions, theories, concepts as well as propositions and related laws. with the formulation of the study problem. Based on these data, it shows that educational material is everything that contains information that has been compiled and the material in education as a whole comes from the Koran and Hadith, including scientific material, especially the theory of atomic glasses. Hadith related to atoms is Hadith Sahih Muslim No. 3947 which contains information regarding the theory of atomic physics and is in line with al-Qquran Saba' verse 3 and the Hadith is authentic. Scientific material, especially the theory of atomic physics, can be used to reveal the mystery of the universe which is proof of the power of Allah SWT.